Noxious radiant heat evokes bi-component nociceptive withdrawal reflexes in spinal cord injured humans—A clinical tool to study neuroplastic changes of spinal neural circuits - Franz, Steffen; Heutehaus, Laura; Tappe-Theodor, Anke; Weidner, Norbert; Treede, Rolf-Detlef; Schuh-Hofer, Sigrid (Frontiers in Human Neuroscience, 2023)
Investigating nocifensive withdrawal reflexes as potential surrogate marker for the spinal excitation level may widen the understanding of maladaptive nociceptive processing after spinal cord injury (SCI). The aim of this prospective, explorative cross-sectional observational study was to investigate the response behavior of individuals with SCI to noxious radiant heat (laser) stimuli and to assess its relation to spasticity and neuropathic pain, two clinical consequences of spinal hyperexcitability/spinal disinhibition. Laser stimuli were applied at the sole and dorsum of the foot and below the fibula head. Corresponding reflexes were electromyography (EMG) recorded ipsilateral. Motor responses to laser stimuli were analyzed and related to clinical readouts (severity of injury/spasticity/pain), using established clinical assessment tools. Twenty-seven participants, 15 with SCI (age 18-63; 6.5 years post-injury; AIS-A through D) and 12 non-disabled controls, (NDC; age 19-63) were included. The percentage of individuals with SCI responding to stimuli (70–77%; p<0.001), their response rates (16-21%; p<0.05) and their reflex magnitude (p<0.05) were significantly higher compared to NDC. SCI-related reflexes clustered in two time-windows, indicating involvement of both A-delta- and C-fibers. Spasticity was associated with facilitated reflexes in SCI (Kendall-tau-b p≤0.05) and inversely associated with the occurrence/severity of neuropathic pain (Fisher’s exact p<0.05; Eta-coefficient p<0.05). However, neuropathic pain was not related to reflex behavior. Altogether, we found a bi-component motor hyperresponsiveness of SCI to noxious heat, which correlated with spasticity, but not neuropathic pain. Laser-evoked withdrawal reflexes may become a suitable outcome parameter to explore maladaptive spinal circuitries in SCI and to assess the effect of targeted treatment strategies. Registration: https://drks.de/search/de/trial/DRKS00006779